VIRGINIA WOOLF'S AESTHETIC VIEWS AND THE CONCEPTION OF MODERNIST PROSE - Xojimirzayeva Gulmira Baxriddin qizi (International Journal of Literature and Language Studies, 2026)
Annotation: This article provides a broad analysis of Virginia Woolf's aesthetic views and the formation of her conception of modernist prose. Her manifesto-articles "Modern Fiction" (1925) and "Mr Bennett and Mrs Brown" (1923), which constitute the theoretical foundation of Woolf's work, are analyzed, and their connection with her artistic practice is shown. Woolf's critique of Edwardian fiction, her concept of inner reality and "moments of being," as well as the influences of Bergson, James, and Roger Fry, are examined. The study evaluates Woolf's aesthetic conception within the context of English modernism and demonstrates its artistic expression in her novels "Mrs Dalloway" and "To the Lighthouse."